Nordic Regional Report : 2013 Cluster Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This paper examines 2013 Cluster Consultation-a Nordic Regional IMF staff report. Denmark, Finland, Norway, and Sweden that form the Nordic region share a set of strong economic and social institutions and policies, with emphasis on education, high income equality, high employment, innovative and competitive business environment, et cetera The IMF report suggests that strong national financial sector policies and regional cooperation would help mitigate common challenges and shared risks. Cooperative regional policies, such as introducing binding macroprudential minima and clear ex ante burden-sharing arrangements are expected to help limit the costs from any large bank failures.